1996
DOI: 10.1037/1196-1961.50.3.324
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition-of-return at multiple locations in visual space.

Abstract: Inhibition-of-return is thought to be a visual search phenomenon characterized by delayed responses to targets presented at recently cued or recently fixated locations. We studied this inhibition effect following the simultaneous presentation of multiple location cues. The results indicated that response inhibition can be associated with as many as four locations at the same time. This suggests that a purely oculomotor account of inhibitionof-return is oversimplified. In short, although oculomotor processes ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
47
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 24 publications
6
47
1
Order By: Relevance
“…However, the role ofthe number ofpossible target locations on inhibition of return has not been examined in depth. Wright and Richard (1993) found equal magnitudes of inhibition while varying the number of simultaneously cued locations, but the present results suggest that the number of potential target locations may have a significant impact on the magnitude of the inhibitory effect.…”
Section: Resultscontrasting
confidence: 47%
“…However, the role ofthe number ofpossible target locations on inhibition of return has not been examined in depth. Wright and Richard (1993) found equal magnitudes of inhibition while varying the number of simultaneously cued locations, but the present results suggest that the number of potential target locations may have a significant impact on the magnitude of the inhibitory effect.…”
Section: Resultscontrasting
confidence: 47%
“…Indeed, in studies in which an empty environmental locus is cued and attention is not oriented to a cued object, the size ofthe effect is quite small. For example, in Wright and Richards's (1996) procedure, in which the spatial locations were not marked by visible peripheral boxes, only 15 msec of lOR was observed in the procedure most similar to that reported here. This compares with the more typical 40-to 50-msec effect observed when peripheral boxes act as place holders (see, e.g., Posner & Cohen, 1984).…”
supporting
confidence: 63%
“…Abrams and Pratt (1996) noted, however, that the subjects in the Tipper et a1. (1996) study might have grouped each of the cued locations into one contiguous region of inhibited space (see also Wright & Richard, 1996). Consistent with this idea, Abrams and Pratt (1996) showed that when three locations were cued in a manner that could preclude spatially contiguous grouping, lOR resided at only the most recently cued location.…”
supporting
confidence: 50%